Cancer cachexia: impact, mechanisms and emerging treatments. Issue 2 (25th October 2012) - Vaughan, Vanessa C.; Martin, Peter; Lewandowski, Paul A.
Abstract : Many forms of cancer present with a complex metabolic profile characterised by loss of lean body mass known as cancer cachexia. The physical impact of cachexia contributes to decreased patient quality of life, treatment success and survival due to gross alterations in protein metabolism, increased oxidative stress and systemic inflammation. The psychological impact also contributes to decreased quality of life for both patients and their families. Combination therapies that target multiple pathways, such as eicosapentaenoic acid administered in combination with exercise, appetite stimulants, antioxidants or anti‐inflammatories, have potential in the treatment of this complex syndrome and require further development.